PEMBELAJARAN DARING BERBASIS STUDENT LEARNING CENTERED DI PERGURUAN TINGGI: TINJAUAN PEMBELAJARAN DI MASA PANDEMI COVID 19 - Masitoh, Dewi (STAI Darul Qalam Tangerang, 2022)
This study aims to describe and analyze online learning based on student learning centered in universities as a review of learning in the emergency period of the covid 19 pandemic. Data collection techniques are through observation, then analyze the data that has been collected from the beginning of the study to the end of the study with data reduction techniques. , presentation of data, and drawing conclusions. The results of this study indicate that online learning based on student learning centered is carried out in the Department of Islamic Religious Education, Faculty of Tarbiyah and Teacher Training (FTIK) IAIN Metro Lampung in the second semester of class A and B in the IAD IBD ISD course using several learning models to support learning activities based on student learning centered, namely Discovery Learning, Cooperative Learning, Collaborative Learning, Small Group Discussion. The four models greatly help the student learning process which is carried out online during the COVID-19 pandemic